The Influence Of Work Discipline And Work Facilities On Employee Performance At Pt. Parsaoran Global Datatrans Branch Tasikmalaya - Winda Windiyani; Rita Tri Yusnita; Mila Karmila (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
This study aims to determine the effect of Work Discipline and Work Facilities on Employee Performance at PT. Parsaoran Global Datatrans Cabang Tasikmalaya. The research method used in this study is a quantitative method with descriptive analysis method. Data collection techniques were obtained directly through questionnaires which were distributed to 50 employee respondents PT. Parsaoran Global Datatrans Cabang Tasikmalaya by using saturated sampling techniques and using the entire population. The data analysis tool used in this study is multiple regression analysis using SPSS software version 25. The results show that: Work Discipline and Work Facilities simultaneously have a significant effect on Employee Performance PT. Parsaoran Global Datatrans. Work Discipline partially has a significant effect on employee performance PT. Parsaoran Global Datatrans and Work Facilities partially have a significant effect on Employee Performance at PT. Parsaoran Global Datatrans Cabang Tasikmalaya.